2016
DOI: 10.3390/molecules21081060
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Enzyme-Free Biomimetic Sensors for Natural Phenol Detection

Abstract: Abstract:The development of sensors and biosensors based on copper enzymes and/or copper oxides for phenol sensing is disclosed in this work. The electrochemical properties were studied by cyclic and differential pulse voltammetry using standard solutions of potassium ferrocyanide, phosphate/acetate buffers and representative natural phenols in a wide pH range (3.0 to 9.0). Among the natural phenols herein investigated, the highest sensitivity was observed for rutin, a powerful antioxidant widespread in functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The sensor can be characterized by high sensitivity and selectivity for rutin (LR of 1 to 120 µM and LOD of 0.4 µM) and catechol (LR of 10 to 600 µM) (Table 11) that is better compared to laccase-based biosensors. Garcia and coauthors [272] reported the construction of a CPS2 (copper oxide-based carbon paste) biomimetic sensor for phenol, rutin and catechol determination in natural samples, such as dried extracts of red fruits and coffee. The enhanced sensitivity towards catechol as a model substrate correlated to the amount of incorporated copper oxide, resulting in improvement of electroactive surface area and electrocatalytic ability os the sensor.…”
Section: Laccase-mimicking Nanozymesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensor can be characterized by high sensitivity and selectivity for rutin (LR of 1 to 120 µM and LOD of 0.4 µM) and catechol (LR of 10 to 600 µM) (Table 11) that is better compared to laccase-based biosensors. Garcia and coauthors [272] reported the construction of a CPS2 (copper oxide-based carbon paste) biomimetic sensor for phenol, rutin and catechol determination in natural samples, such as dried extracts of red fruits and coffee. The enhanced sensitivity towards catechol as a model substrate correlated to the amount of incorporated copper oxide, resulting in improvement of electroactive surface area and electrocatalytic ability os the sensor.…”
Section: Laccase-mimicking Nanozymesmentioning
confidence: 99%
“…Garcia and coauthors [ 272 ] reported the construction of a CPS2 (copper oxide-based carbon paste) biomimetic sensor for phenol, rutin and catechol determination in natural samples, such as dried extracts of red fruits and coffee. The enhanced sensitivity towards catechol as a model substrate correlated to the amount of incorporated copper oxide, resulting in improvement of electroactive surface area and electrocatalytic ability os the sensor.…”
Section: Laccase-mimicking Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laccase biosensors have been recently developed to monitor some toxic and/or harmful chemicals like phenolic compounds . They have also been tested for immune assays, hormone monitoring in clinical diagnosis and the quantitative analysis of beverages .…”
Section: Laccases As Versatile Enzymes: Traditional and New Industriamentioning
confidence: 99%
“…The immobilization of laccase enzymes on the surfaces of different materials to constitute a biosensing platform is however, a critical factor in the development of bioelectrochemical sensing devices. In this sense, copper oxide nanoparticles, nanocomposites containing molybdenum disulfide, graphene quantum dots and ionic liquid membranes have become compatible matrices for laccase immobilization in biosensing devices.…”
Section: Laccases As Versatile Enzymes: Traditional and New Industriamentioning
confidence: 99%